Gene Therapy in the Management of Erectile Dysfunction (ED): Past, Present, and Future - Arnold Melman; Kelvin P. Davies (The Scientific World Journal)
In the past, many researchers considered viral vectors to be the most promising candidates to transfer genetic material into the corpora for the treatment of erectile dysfunction. However, at present, no viral vectors have progressed to human trials. In contrast, the use of naked gene therapy, a plasmid expressing the human Maxi-K potassium channel, is the only gene therapy treatment to be evaluated in clinical phase I trials to date. The success of these studies, proving the safety of this treatment, has paved the way for the development of future gene transfer techniques based on similar transfer methods, as well as novel treatment vectors, such as stem cell transfer.